OPTIMIZATION OF DIGITAL APPLICATIONS IN HEALTH LICENSING SERVICES AT THE ONE-STOP INVESTMENT AND INTEGRATED SERVICE OFFICE OF SINTANG DISTRICT: OPTIMALISASI APLIKASI DIGITAL DALAM PELAYANAN PERIZINAN KESEHATAN - Abang Zainudin; Widya Ananda Putri (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
Licensing of health worker practices is regulated in several laws and regulations. One of them is Law Number 36 of 2014 concerning Health Workers. The Sintang Regency Investment and One-Stop Integrated Service Office (DPMPTSP) has a role as an institution that organizes integrated licensing services in Sintang Regency and is required to provide licensing services that are fast, accurate, with costs according to the provisions, transparently to the community. In order to simplify and accelerate licensing services, the Sintang District DPMPTSP implements the Digital Public Service Mall application. The application makes a positive contribution in improving the efficiency and effectiveness of the licensing process. In terms of efficiency, digitization speeds up service time, reduces administrative workload, and saves operational costs. In terms of effectiveness, the application accelerates the process of document submission and verification. However, in the aspect of satisfaction, although the majority of users find it helpful, there are still technical obstacles and limited understanding of the use of the application, especially for users with low digital literacy, therefore the DPMPTSP of Sintang Regency is expected to carry out regular socialization activities and assistance to users of the Digital Public Service Mall application service.